Implikasi Putusan Mahkamah Konstitusi dalam Pemakzulan Presiden dan/atau Wakil Presiden di Indonesia - Siregar, Lisdhani Hamdan (Jurnal Konstitusi, 2012)
The one of Constitutional Court authority, commonly it called as a duty, has gived a verdict for Indonesian Legislative Assembly opinion about guess of inlegallity by doing President and or without Vice President. The characteristic of Constitutional Court’s verdict has been juridical final. As relative character of verdict, Constitutionan Court’s Verdict has not had a strength binding for The People Advisory Assembly as the last institution in settlement process for dismissal President and or without Vice President in their period to follow the Constitutional Court’s verdict, except to held plenary session like Indonesian Legislative Assembly’s opinion. It was a consequency of Article 7B Paragraph (6) Indonesian Constitution of 1945.